Pharmacokinetics of Dantrolene in the Plasma Exchange Treatment of Malignant Hyperthermia in a 14-Year-Old Chinese Boy: A Case Report and Literature Review - Li, Xiaoxiao; Li, Chao; Zhou, Yang; Li, Zhengqian; Xiong, Xin; Wang, Chuhui; Zhou, Congya; Han, Bin; Yang, Li; Guo, Xiangyang (Frontiers in Medicine, 2022)
Malignant hyperthermia (MH) is a rare life-threatening response that is triggered by exposure to specific anesthetics commonly used during surgical interventions. Dantrolene is a well-known drug used as the first-line therapy for MH. A 14-year-old Chinese boy with a mutation in type 1 Ryanodine receptor (RyR1) whose muscle biopsy diagnosis was central core disease (CCD) had an occurrence of MH after a cervical spine surgery, during which he was placed under general anesthesia without volatile anesthetics or succinylcholine. The MH crisis treatment workflow was started and intravenous dantrolene was used, which was soon combined with sequent continuous veno-venous hemofiltration (CVVH) and plasma exchange (PE) therapy. We explored the pharmacokinetic profile of dantrolene during PE treatment. It showed that a one-compartment model with first-order kinetics was sufficient to characterize dantrolene pharmacokinetics (PK). The renal clearance estimate for dantrolene was 0.33 mL/(min*kg) and the volume of distribution was 0.51 L/kg. Though a 4-h PE elevated about 27% off-clearance for dantrolene, it eliminated extra dantrolene by a mere 4% of the area under the curve (AUC). We made no recommendation with respect to adjusting dantrolene dosing for MH adolescents with a 4-h PE.